Nikolay Gumilev’s The lost tram: literary-mythological and historical-biographical contexts of the tram route - Lukashova, Alina (Vilnius University Open Series, 2024)
The article discusses various interpretations of Nikolai Gumilev’s poem The Lost Tram. Attention is paid to the nuances of the use of ancient plots in the poem. Important questions about the date of writing the work are raised. Particular attention is paid to the mysterious route through three bridges. The three rivers mentioned in the poem – the Neva, the Nile, and the Seine – are usually regarded as symbols of radical transformations in the life of people and society (the October Revolution, the exodus of Jews from Egypt, and the Great French Revolution). The article suggests that the event associated with the Nile could not have been a page from the Jewish history, but rather the revolution in Egypt in the first half of the 20th century. Thus, the symbolism of the tram expands to the symbol of an abstract world revolution.
Keywords: Nikolay Gumilev; Hades; Orpheus; tram; Nile; revolution